Rethinking the way of doing business: A reframe of management structures for developing corporate sustainability - Nunhes, Thaís Vieira [UNESP]; Bernardo, Merce; José de Oliveira, Otávio [UNESP] (MDPI, 2020)
Corporate sustainability (CS) literature has gone through a period of intense development. The moment is favorable to gather these contributions to consistently advance the state-of-the-art in CS and, also, discuss them in application to real contexts. The main objective of the paper is to systematize, through a literature review using content analysis of the 30 most cited articles from 2007 to 2017, the guiding pillars of CS management. A systematic search for papers was carried out in Scopus and Web of Science, and the initial screening of the papers was assisted by the coding software, MAXQDA 2018, through which the authors structured and analyzed their main insights, contributions, and conclusions. After getting acquainted with the sample, an in-depth reading of the texts was conducted and 60 CS elements were identified. The elements cited in the relevant literature were grouped into six pillars related to corporate sustainability strategy, corporate governance, human resources management, knowledge and innovation management, measurement, disclosure, and independent assurance, and management systems, and integrated management systems. The main contribution of this paper is to identify the management pillars of CS in a systematic way to consistently advance the state-of-the-art in the subject. Also, this study provides understanding to managers on the main aspects that make up the integration of this construct in the companies.
Keywords: Business sustainability; Content analysis; Corporate sustainability; Literature review; Sustainable management